A biochemical study into the selective recruitment of Rubisco activase into the pyrenoid - How, Jian Boon (Nanyang Technological University, 2024)
Photoautotrophs have evolved various strategies to maximize the activity of the error-prone and sluggish carbon fixation enzyme ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco). This includes a CO2 concentrating mechanism (CCM), whose biophysical implementation involves the sequestration of Rubisco in a microcompartment. Like most unicellular microalgae, the green algae Chlamydomonas reinhardtii sequesters Rubisco in the pyrenoid, a membraneless microcompartment in the chloroplast. Pyrenoid assembly requires heterotypic liquid-liquid phase separation (LLPS) between the multivalent Rubisco linker protein Essential Pyrenoid Component 1 (EPYC1) and C. reinhardtii Rubisco (CrRubisco). The AAA+ molecular chaperone Rubisco activase (Rca) is also localized within the pyrenoid matrix, where Rca ensures continuous flux of carbon fixation by Rubisco. Here, we characterized the recruitment of C. reinhardtii Rca (CrRca) into the C. reinhardtii pyrenoid by utilizing our in vitro reconstitution consisting of EPYC1 and CrRubisco. After extensive efforts, we purified functional recombinant CrRca. Through gel electrophoresis and fluorescence microscopy, we reveal that the minimal system consisting of EPYC1 and CrRubisco is sufficient to recruit CrRca. CrRca also unexpectedly undergoes heterotypic LLPS with EPYC1 to form liquid-like condensates, a process that we demonstrate to be likely non-specific. Mutagenesis experiments on CrRca indicated that its conserved N-domain is essential for selective partitioning into EPYC1-CrRubisco condensates through specific CrRca-CrRubisco interactions. Furthermore, fusing a single CrRca N-domain to blue fluorescent protein (mTagBFP2) was sufficient to target mTagBFP2 into these condensates via specific interactions with CrRubisco. These findings contribute towards understanding the selective localization of proteins into the pyrenoid and its underlying interactions. The conserved biochemical significance of the CrRca N-domain with other green-type Rca also suggests that during evolution, pre-existing protein-protein interactions are utilized for selective partitioning of proteins into biomolecular condensates. This study will inform ongoing synthetic biology efforts towards engineering a biophysical CCM in crop plants to improve its photosynthetic efficiency, thereby increasing crop yields.